2012
DOI: 10.1111/ggi.12017
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in elderly patients: New insight into an old disorder

Abstract: Anemia is an important healthcare concern among the elderly. In these patients, the anemia is often mild, with a hemoglobin level >10 g/dL. It is usually well tolerated, but might be responsible for several proteiform and/or atypical presenting complaints. In the elderly, anemia is usually of multifactorial origin, including chronic inflammation, chronic kidney disease, nutrient deficiencies and iron deficiency (approximately two-thirds of all cases). The remaining cases are unexplained (unknown etiology). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 42 publications
(151 reference statements)
7
92
1
6
Order By: Relevance
“…Furthermore, the decreased erythroid colony forming potential of Mutator HSCs, combined with a severe maturation delay, is also typical for HSCs extracted from aged people 47 . Anaemia is an important class of human disorders affecting over 50% of 80-year-olds in the population 48 , but only 30% of agingrelated anaemia can be explained by iron deficiency 49 . Since mtDNA mutations accumulate in normal aging humans 50 this raises the question whether aging-related anaemia in human population might also have mitochondrial contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decreased erythroid colony forming potential of Mutator HSCs, combined with a severe maturation delay, is also typical for HSCs extracted from aged people 47 . Anaemia is an important class of human disorders affecting over 50% of 80-year-olds in the population 48 , but only 30% of agingrelated anaemia can be explained by iron deficiency 49 . Since mtDNA mutations accumulate in normal aging humans 50 this raises the question whether aging-related anaemia in human population might also have mitochondrial contribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, GPs may have considered these patients too vulnerable for extensive tests due to, for example, advanced age and/or comorbidities, or the lack of consequences in these frail patients. 24 Comparable studies analysing the underlying causes of ACD have investigated hospitalised populations, whereas no data are available for community-dwelling adults with ACD. In this study, the most common underlying causes of ACD were infections, autoimmune inflammation, and malignancies; this is in line with data from hospitalised patients with ACD.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In clinical practice, an Hb level <10 g/dL is often considered to be a cut of level where investigation in the elderly ("anemia to explore"), and treatment should be performed [7]. Indeed, at this Hb level, several recent studies have shown a beneit from investigating the anemia and for treating, in regard to the frequency of discovery of a curable etiology [7].…”
Section: Deinition Of Nutritional Anemiamentioning
confidence: 99%
“…Indeed, at this Hb level, several recent studies have shown a beneit from investigating the anemia and for treating, in regard to the frequency of discovery of a curable etiology [7].…”
Section: Deinition Of Nutritional Anemiamentioning
confidence: 99%
See 1 more Smart Citation